2002
DOI: 10.1021/jp021045k
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evidence for Surface Nucleation of Solid Polar Stratospheric Cloud Particles

Abstract: Nitric acid-containing cloud particles, known as polar stratospheric clouds, play an important role in the springtime ozone destruction over the polar regions. Nitric acid initially condenses in the polar stratosphere to form supercooled solution droplets of mainly nitric acid and water with trace amounts of sulfuric acid. Nitric acid dihydrate (NAD) and nitric acid trihydrate (NAT) later crystallize from this supercooled solution phase to form solid polar stratospheric cloud particles. Until now, experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
201
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(213 citation statements)
references
References 45 publications
4
201
8
Order By: Relevance
“…Finally it is interesting to mention the actual freezing rates we have found in the simulations, using the rates of Tabazadeh et al (2002) reduced by 100. The highest values we obtain are of order ∼10 m −2 s −1 × surface area.…”
Section: Nat Freezing Mechanismmentioning
confidence: 96%
See 3 more Smart Citations
“…Finally it is interesting to mention the actual freezing rates we have found in the simulations, using the rates of Tabazadeh et al (2002) reduced by 100. The highest values we obtain are of order ∼10 m −2 s −1 × surface area.…”
Section: Nat Freezing Mechanismmentioning
confidence: 96%
“…homogeneous volume dependent nucleation of ICE out of STS 3-4 K below the ice frost point temperature T ice (Koop et al, 2000), and homogeneous surface dependent nucleation of nitric acid dihydrate (NAD) out of STS (Tabazadeh et al, 2002) above T ice , followed by (assumed) instantaneous conversion of NAD to NAT. The NAD homogeneous nucleation rates have been reduced by a factor of 100 following recent studies (Knopf et al, 2002;Voigt et al, 2005;Höpfner et al, 2006b).…”
Section: The Psc Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Tabazadeh et al [43] re-analyzed the experimental data on the homogeneous freezing rates of concentrated aqueous nitric acid solution droplets, which constitute polar stratospheric clouds. They found that surface-based rate expressions are consistent with all the considered laboratory data [44]- [48] and that the homogeneous nucleation process occurring in atmospheric droplets may be a surface-rather than a volume-related rate process.…”
Section: Reported Datamentioning
confidence: 99%